Design and optimization of an air-based phase change cold storage unit through cascaded construction for emergency cooling in IDC. (15th February 2022) - Zheng, Ziao; Huang, Bin; Lu, Gaofeng; Zhai, Xiaoqiang
Abstract: This paper proposed an air-based phase change cold storage (APCCS) unit for emergency cooling in Internet Data Center (IDC). Firstly, the self-developed phase change material (PCM) applicable to IDC cooling was prepared. Then, experiments including both charging and discharging process of the APCCS unit were carried out. Next, a numerical model was developed to evaluate the thermal performance during the discharging process for emergency cooling and was validated with experimental results. Further, a cascaded arrangement of PCM from one to five stages was constructed and optimized based on exergy analysis. The results demonstrated that the average exergy efficiency has increased by 7.8% together with an increase of 19 kJ on exergy from single stage to five stages. In addition, heat transfer optimization was performed by rearranging the (PCM) containers from in-line to staggered form. A four-stage staggered arrangement outperformed the single-stage unit in terms of an increase of 25 kJ on exergy as well as nearly 10% on average exergy efficiency. Meanwhile, the discharging rate for the four-stage staggered unit could be maintained above 2.5 kW for 30 min, providing enough cooling capacity for a typical cabinet with 10 2U servers (intel M70KLP4S2UHH) in IDC during electricity emergency. Highlights: An air-based phase change cold storage unit is proposed for emergency cooling in IDC. Optimization of the cascaded construction is performed based on exergy analysis. The effective cooling time is extended through cascaded construction and heat transfer optimization.